Makna Denotasi, Konotasi, dan Mitos dalam Film Dokumenter “Desa Wae Rebo” - Ludmila Navita; Anisti Anisti; Tuty Mutiah (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
This study explores the denotative, connotative, and mythological meanings embedded in the documentary film about Wae Rebo Village using Roland Barthes' semiotic theory. The film highlights the life of the indigenous Wae Rebo community in Flores, East Nusa Tenggara, which is renowned for its traditional Mbaru Niang houses and its well-preserved ancestral culture. The analysis focuses on scenes that represent elements of culture, communal identity, and the community’s connection with nature and their ancestors. The findings reveal that, on a denotative level, the film depicts daily activities, traditional ceremonies, and distinctive architectural forms. On the connotative level, it reflects values of togetherness, spirituality, and harmony with nature. In the realm of myth, the film presents an image of cultural purity and the idealization of village life untouched by modernity. This study contributes to a deeper understanding of cultural meaning construction in visual media, particularly documentary films, through a semiotic approach.